Doping in uporaba prehranskih dopolnil v športu - Žiberna, Lovro (Farmacevtski vestnik, 2017)
The presence of prohibited substances or their metabolites or their biomarkers in an athlete's biological sample is a violation of anti-doping rules. List of pharmacologically active substances not allowed in sport is registered in the Prohibited List, which is a public document issued annually by the World Anti-Doping Organization (WADA). In case of pathology requiring pharmacological treatment, the athlete can acquire therapeutic use exemption certificate, which allows the use of otherwise prohibited substance. Since an athlete himself is responsible for all the substances that come into his body, whatever its intended use, it is also important to be familiar with the dangers of inadvertent doping. The most common form of inadvertent doping is the use of contaminated food supplements.
Keywords: antidoping; detoksifikacija jeter; doping; inadvertend doping; nenamerni doping